Assessment of corneal curvature using verion optical imaging system: a comparative study. (20th February 2016) - Lauschke, Jenny L; Lawless, Michael; Sutton, Gerard; Roberts, Timothy V; Hodge, Christopher
Abstract: Background: Keratometry is a critical determinant of the postoperative refractive outcome. This study evaluates the comparability of keratometry measurements obtained using the Verion Optical Imaging System with devices used in current clinical practice. Further, it determines the interobserver reliability of the Verion Optical Imaging System. Design: Retrospective analysis of patient data Participants: Keratometric data was obtained from 100 patients presenting for pre‐operative evaluation. Furthermore, repeatability and reproducibility were assessed using 15 healthy volunteers. Methods: Corneal curvature values acquired by the Verion Optical Imaging System were compared with existing keratometry devices including autokeratometry, partial coherence interferometry (IOLMaster) and Scheimpflug corneal topography (Pentacam). Main Outcome Measures: Direct comparison of corneal power, cylinder, axis of astigmatism and vector analysis were performed using correlation and Bland–Altman analyses. Reproducibility and reliability of the device were assessed using within‐subject standard deviation and intraclass correlation coefficients for experienced and inexperienced technicians. Results: There was no statistically significant difference between Verion values and those obtained by other methods in relation to mean keratometry, corneal astigmatism, steep meridian and vector analyses ( P > 0.05). Bland–Altman plots showed narrow limits of agreement for keratometry and astigmatism and wider agreement for steep meridian. Intraoperator reliability for both experienced and inexperienced operators and interoperator reproducibility showed no statistically significant differences between values. Conclusion: Measurements show no significant difference from those obtained by the other devices. This suggests the Verion system is en par with instruments used in current clinical practice. The Verion Optical Imaging System produces repeatable data with no difference related to operator experience.